The Role of Preload and Leakage Correction in Gadolinium-Based Cerebral Blood Volume Estimation Determined by Comparison with MION as a Criterion Standard - Boxerman, J. L.; Prah, D.E.; Paulson, E.S.; Machan, J.T.; Bedekar, D.; Schmainda, K.M. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: Contrast extravasation in DSC-MRI potentiates inaccurate and imprecise estimates of glioma rCBV. We tested assertions that preload and postprocessing algorithms minimize this error by comparing Gd-rCBV using permutations of these 2 techniques with criterion standard rCBV using MION, an intravascular agent. MATERIALS AND METHODS: We imaged 7 Fisher rats with 9L gliosarcomas, by using 3T gradient-echo DSC-MRI with MION (2.0 mg Fe/kg) and staged injection of Gd-diethylene triamine pentaacetic acid: a 0.1-mmol/kg bolus provided no preload (P−) data and served as preload (P+) for a subsequent 0.2-mmol/kg bolus. We computed MION-rCBV (steady-state ΔR2*, tumor versus normal brain) and Gd-rCBV ΔR2* [t] integration) without (C−) and with (C+) postprocessing correction, thereby testing 4 correction permutations: P−C−, P−C+, P+C−, and P+C+. We tested whether each permutation reduced bias and variance of the Gd/MION rCBV differences by using generalized estimating equations and Fmax statistics (P < .05 significant). RESULTS: Gd-rCBV progressively better approximated MION-rCBV with increasing leakage correction. There was no statistically significant bias for the mean percentage deviation of Gd-rCBV from MION-rCBV for any correction permutation, but there was significantly reduced variance by using P+C− (22-fold), P−C+ (32-fold), and P+C+ (267-fold) compared with P−C−. P+C+ provided significant additional variance reduction compared with P+C− (12-fold) and P−C+ (8-fold). Linear regression of Gd-rCBV versus MION-rCBV revealed P+C+ to have the closest slope and intercept compared with the ideal, substantially better than P+C−. CONCLUSIONS: Preload and postprocessing correction significantly reduced the variance of Gd-rCBV estimates, and bias reduction approached significance. Postprocessing correction provide significant benefit beyond preload alone. C−without leakage correction algorithm appliedC+with leakage correction algorithm appliedCIconfidence intervalDSCdynamic susceptibility contrastGdgadoliniumK2linear coefficient in the fitting algorithm used to correct for contrast agent extravasation in CBV estimates as defined in References 21 and 22MIONmonocrystalline iron oxide nanoparticle intravascular contrast agentP−without administration of preload contrast agent doseP+with administration of preload contrast agent doserCBVrelative cerebral blood volume